The future of gobal mobility: Why we need a debate about multilateral and digital solutions to prevent the Global South from being excluded from international travel - Steffen Angenendt; Karl Steinacker (Stiftung Wissenschaft und Politik (SWP), 2022)
The Covid-19 pandemic has greatly reduced international travel. The economic, social and human consequences of border closures and travel restrictions cannot be fully estimated yet, but they are dramatic. The gap is widening between countries of the Global North, which want to control travel and prevent unregulated mobility, and those of the Global South, which are demanding more legal mobility for their citizens. The freedom to travel is a desirable good that all should be able to access, and is also the object of political negotiations. Unilateral decisions should be complemented or superseded by international agreements between countries about common rules and procedures for a trust-based system. In the meantime, countries should modernise their visa processes and build digital identification systems that create trust. This applies to Germany as well, especially since the coalition government has decided to speed up the issuing of visas.
Keywords: 380